Intravenous delivery of granulocyte-macrophage colony stimulating factor impairs survival in lipopolysaccharide-induced sepsis - Krebs, Jörg; Hillenbrand, Alexander; Tsagogiorgas, Charalambos; Patry, Christian; Tönshoff, Burkhard; Yard, Benito A.; Beck, Grietje; Rafat, Neysan (PLOS ONE, 2019)
Background Cell-based therapies with bone marrow-derived progenitor cells (BMDPC) lead to an improved clinical outcome in animal sepsis models. In the present study we evaluated the ability of granulocyte macrophage-colony stimulating factor (GM-CSF) to mobilize BMDPC in a lipopolysaccharide (LPS)-induced sepsis model and thereby its potential as a novel treatment strategy. Methods Male Wistar rats received LPS (25μg/kg/h for 4 days) intravenously and were subsequently treated with GM-CSF 12.5μg/kg (0h,24h,48h,72h). As control groups, rats were infused with sodium chloride or GM-CSF only. Clinical and laboratory parameters, proinflammatory plasma cytokines as well as BMDPC counts were analyzed. Cytokine release by isolated peripheral blood mononuclear cells from rat spleen upon incubation with LPS, GM-CSF and a combination of both were investigated in vitro. Results In vivo, rats receiving both LPS and GM-CSF, showed a reduced weight loss and increased mobilization of BMDPC. At the same time, this regime resulted in an increased release of proinflammatory cytokines (IL-6, IL-8) and a significantly increased mortality. In vitro, the combination of LPS and GM-CSF showed a significantly increased IL-6 release upon incubation compared to incubation with LPS or GM-CSF alone. Conclusions GM-CSF did not have a beneficial effect on the clinical course in our LPS-induced sepsis model. It synergistically promoted inflammation with LPS and probably thereby impaired survival.